An overview on structural health monitoring: from the current state-of-the-art to new bio-inspired sensing paradigms. (19th July 2019) - Masciotta, Maria-Giovanna; Barontini, Alberto; Ramos, Luís F.; Amado-Mendes, Paulo; Lourenço, Paulo B.
In the last decades, the field of structural health monitoring (SHM) has grown exponentially. Yet, several technical constraints persist, which are preventing full realisation of its potential. To upgrade current state-of-the-art technologies, researchers have started to look at nature's creations giving rise to a new field called 'biomimetics', which operates across the border between living and non-living systems. The highly optimised and time-tested performance of biological assemblies keeps on inspiring the development of bio-inspired artificial counterparts that can potentially outperform conventional systems. After a critical appraisal on the current status of SHM, this paper presents a review of selected works related to neural, cochlea and immune-inspired algorithms implemented in the field of SHM, including a brief survey of the advancements of bio-inspired sensor technology for the purpose of SHM. In parallel to this engineering progress, a more in-depth understanding of the most suitable biological patterns to be transferred into multimodal SHM systems is fundamental to foster new scientific breakthroughs. Hence, grounded in the dissection of three selected human biological systems, a framework for new bio-inspired sensing paradigms aimed at guiding the identification of tailored attributes to transplant from nature to SHM is outlined.